Estimation of Carbon Stock in Sungai Merah Protection Forest, Musi Banyuasin Regency of South Sumatra Province - Lulu Yuningsih; Ifran D. Imanda; Ayu Wulandari; Delfi Lensari; Jun Harbi (Sriwijaya Journal of Environment, 2020)
Calculation and estimation of carbon stocks in various types of forests and ecosystems in Indonesia has been widely practiced. However, the availability of carbon stock information for some locations in the remaining forest area in South Sumatra Province is still very limited. This study aim to measuring the carbon storage potential and the ratio between the carbon storage value derived from the interpretation of satellite imagery and the storage of carbon stock from the field calculation. The method used is to calculate the estimation of carbon stock through satellite imagery interpretation and field measurement. The largest estimation of carbon stock through satellite image interpretation was found in secondary forest cover type with yield 896,234 ton/c/ha, followed by plantation land type with a yield of 147.104 ton/c/Ha and the smallest is open land cover with value yield of 2.883 tons/c/ha. While carbon stocks through field measurement yield 429,181 ton/c/ha of secondary forest cover type, followed by plantation land type with 41,169 ton/c/ha and 4,283 ton/c/ha for open land type. A comparison of carbon stock estimates of the two approaches used, yielding a reference value of 220%. These comparative values can be used to assist in carrying out initial estimates of carbon stocks in some types of land cover, especially for lowland forest types.